Buying military transformation : technological innovation and the defense industry - Dombrowski, Peter J., 1963-; Gholz, Eugene, 1971- (Columbia University Press, 2006)
In Buying Military Transformation, Peter Dombrowski and Eugene Gholz analyze the United States military's ongoing effort to capitalize on information technology. New ideas about military doctrine derived from comparisons to Internet Age business practices can be implemented only if the military buys technologically innovative weapons systems. Buying Military Transformation examines how political and military leaders work with the defense industry to develop the small ships, unmanned aerial vehicles, advanced communications equipment, and systems-of-systems integration t.